Altered Complexity of Spontaneous Brain Activity in Schizophrenia and Bipolar Disorder Patients. Issue 2 (11th February 2021) - Zhang, Nan; Niu, Yan; Sun, Jie; An, Weichao; Li, Dandan; Wei, Jing; Yan, Ting; Xiang, Jie; Wang, Bin
Abstract : Background: Schizophrenia (SC) and bipolar disorder (BP) share elements of symptoms and the underlying neural mechanisms for both remain unclear. Recently, the complexity of spontaneous functional MRI (fMRI) signals in brain activity has been investigated in SC and BP using multiscale sample entropy (MSE) with inconsistent results. Purpose: To perform MSE analysis across five time scales to assess differences in resting‐state fMRI signal complexity in SC, BP, and normal controls (NC). Study Type: Retrospective. Population: Fifty SC, 49 BP, and 49 NC. Field Strength/Sequence: A 3 T, T2* weighted echo planar imaging (EPI) sequence. Assessment: The mean MSEs of all gray matter (GM) and of 12 regions of interest (ROIs) were extracted using masks across the five scales. The regional homogeneity (ReHo) and amplitude of low‐frequency fluctuation (ALFF) in these ROIs were also determined and the relationship between the three measures was investigated. The correlations between cognitive assessment scores and MSE values were also explored. Statistical Tests: Bonferroni correction, One‐way ANOVA, Spearman rank correlation coefficient (r), Gaussian random field (GRF) correction. Results: There were decreased GM MSE values in the patient groups (F = 9.629, P  < 0.05). SC and BP patients demonstrated lower complexity than NCs in the calcarine fissure, precuneus, inferior occipital gyrus, lingual gyrus and cerebellum, and higher complexity in the median cingulate, thalamus, hippocampus, middle temporal gyrus and middle frontal gyrus. There were significant differences between SC and BP patients in the precuneus (F = 4.890, P  < 0.05) and inferior occipital gyrus (F = 5.820, P  < 0.05). Calcarine fissure, cingulate, temporal gyrus, occipital gyrus, hippocampus, precuneus, frontal gyrus, and lingual gyrus MSE values were significantly correlated with both ReHo ( r  > 0.282, P  < 0.05) and ALFF ( r  > 0.278, P  < 0.05). Furthermore, median temporal MSE ( r  = −0.321, P  < 0.05) on scale 3 and ( r  = −0.307, P  < 0.05) on scale 4 and median cingulate MSE ( r  = −0.337, P  < 0.05) on scale 5 was significantly negatively correlated with cognitive assessment scores. Data Conclusion: These data highlight different patterns of brain signal intensity complexity in SC and BP. Level of Evidence: 1 Technical Efficacy: Stage 1